Research in consumer behavior. Vol. 13 - Belk, Russell W. (Bingley, U.K. : Emerald, 2011)
Research in Consumer Behavior presents cutting edge consumer research, whether empirical or conceptual, qualitative or quantitative. The majority of papers in this volume have been selected from the best papers at the 2011 Consumer Culture Theory Conference held in Chicago Illinois in July, 2011. The Conference is the premier event for consumer culture research which tends to be qualitative, ethnographic, and cultural in orientation and draws a variety of scholars from around the world. Many of these scholars are housed in academic marketing department, but they also come from fields of anthropology, sociology, cultural studies, and communications as well as from industry. The papers selected for this volume are those judged to be the best among those selected for the conference from submissions to the conference peer review. This marks the third volume of Research in Consumer Behavior that has been able to publish the top Consumer Culture Theory papers.
Introduction / Russell W. Belk -- Collaborative value co-creation in crowd-sourced online communities : acknowledging and resolving competing commercial and communal orientations / Carol Kelleher, Andrew Whalley, Anu Helkkula -- If you can't stand the heat, get out of the kitchen : foodies resist the cultural authority of the market / Amanda Earley -- Show me the mascot : corralling critters for pedagogic purposes / Stephen Brown -- A typology of consumption communities / Robin Canniford -- Food, love and meta-practices : a study of everyday dinner consumption among single mothers / Susanna Molander -- We dream as we live : consuming / Anu Valtonen -- Buying the girlfriend experience : an exploration of the consumption experiences of male customers of escorts / Aimee Dinnin Huff -- The cultural role of stigmatized youth groups : the case of the Partille Johnnys of Sweden / Emma Lindblad, Jacob Ostberg -- Love and videogames : negotiating relationships with cultural ideals and consumer practices / Mike Molesworth, Rebecca Jenkins, Sue Eccles -- Skating dialectics and flipping genealogy / Soonkwan Hong -- Staring : how Facebook facilitates the breaking of social norms / Ekant Veer -- The modern woman myth as a means of cosmopolitan cultural capital accumulation : a gendered acculturation perspective / Zuzana Chytkova, Dannie Kjeldgaard -- The nouveaux pauvres of liquid modernity / Sofia Ulver-Sneistrup, Jacob Ostberg -- Realistically fake : self-reflexive consciousness, ironic (dis)engagement with hybrid reality television, and their impact on consumption / Vanisha Narsey, Cristel A. Russell.
Keywords: Consumer behavior -- Research